RELATIONSHIP BETWEEN PSYCHOLOGICAL RESILIENCE AND SELF-CARE STRATEGIES OF HEALTHCARE PROFESSIONALS DURING COVID-19 PANDEMIC IN LATVIA - Bundzena-Ervika, Aiva; Mārtinsone, Kristīne; Perepjolkina, Viktorija; Ruža, Aleksejs; Koļesņikova, Jeļena; Rancāns, Elmārs (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
As the worldwide pandemic of Covid-19 continues, health-care professionals (HCP) have been exposed to different hazards, and there is a need to explore psychological resilience in crisis situations, and to give recommendations for its strengthening. The aim of this study was to examine relationship between psychological resilience and self-care strategies in HCP of Latvia, controlling for gender and age during Covid-19 pandemic, and to determine whether the psychological resilience and self-care strategies differ between HCP and professionals in other fields (POF) unrelated to healthcare. Method. The sample consisted of 1723 employees, who during the state of emergency continued to work in their profession; they were divided in two groups - 77 HCP (18 men, 59 women, age M = 46.23 (SD = 14.43)) and 1646 POF (720 men, 926 women, age M = 44.98 (SD = 11.93)) as comparison group. Specific data of national representative cross-sectional online survey (N = 2608), performed in July, 2020, were selected – demographic items, 7 items forming Psychological Resilience Scale and 17 item forming Self–care Strategies Questionnaire (consist of 4 scales: “Spiritual resources”, “Social support”, “Free time activities”, “Time management”). Results. “Time management” was only predictive for Self-care strategy for psychological resilience in both HCP and POF group. Neither age nor gender predicted psychological resilience in HCP group. No statistically significant differences for major variables between HCP and POF were found. Conclusions. The results suggest that performing such Self-care activity as time management can help to promote psychological resilience of the employees regardless of profession. Given the workload of HCP in pandemic, this is an important result. HCP psychological resilience and used self-care strategies during COVID-19 are not different from POF.